2017
DOI: 10.1007/s00148-016-0630-z
|View full text |Cite
|
Sign up to set email alerts
|

Assisted reproductive technology and women’s choice to pursue professional careers

Abstract: We examine the impact of assisted reproductive technology on women's choice to pursue professional careers. We hypothesize that the availability of assisted reproductive technology increases the expected benefits of a professional degree by allowing women to delay childbearing in their 20s and 30s while establishing their careers, thereby reaping greater financial benefit from human capital investment. State-level timing differences in the enactment of laws which mandated infertility treatment coverage in empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Unpublished work by Buckles (2007) presents some evidence evidence that infertility insurance mandates led to increased labor force participation for women under the age of 35 (but a decrease for older women). Kroeger and La Mattina (2017) find an increase in women's participation in "professional" occupations (those requiring a JD, MD, DDS, etc.) in states that passed IVF mandates.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Unpublished work by Buckles (2007) presents some evidence evidence that infertility insurance mandates led to increased labor force participation for women under the age of 35 (but a decrease for older women). Kroeger and La Mattina (2017) find an increase in women's participation in "professional" occupations (those requiring a JD, MD, DDS, etc.) in states that passed IVF mandates.…”
Section: Related Literaturementioning
confidence: 99%
“…This report also shows that Israel, in the first place in 2004, had almost twice as many treatment cycles per million population as Denmark, in second, and almost 8 times as in the US.4 Most of the research using US insurance mandates focuses on the women who themselves use IVF(Velez et al, 2014;Hamilton and McManus, 2012; Schmidt, 2012, 2006;Bundorf et al, 2007;Buckles, 2013;Schmidt, 2007Schmidt, , 2005Machado and Sanz-de Galdeano, 2015). A smaller body of literature looks at the impact on younger women(Ohinata, 2011;Abramowitz, 2017Abramowitz, , 2014Buckles, 2007;Kroeger and La Mattina, 2017). For a complete discussion, see Section 2.5 The policy also impacted treatment of male infertility via access to sperm donation and to ICSI (a procedure that allows to use a single sperm-cell to fertilize an egg), this is "primary" rather than "secondary," meaning age-related, infertility, and thus does not affect time horizons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Publications on the topic of this research are scarce both in domestic and foreign literature. ART studies are divided into: studies of factors of ART usage (Adamson 2009;Bennett 2016;Wu 2019;Dadaeva, Baranova 2019); studies of the impact of different types of insurance on the results of using the technology (Baker et al 2007;Hamilton, McManus 2011;Bitler, Schmidt 2012;Buckles 2013;Crawford et al 2016); estimates of the impact of ART on birth rates (Schmidt 2005(Schmidt , 2007Burcin et al 2014;Machado, Sanz-de-Galdeano 2015;Vasilyeva, Peregontseva 2016); assessment of the impact of ART development on reproductive behaviour (Abramowitz 2014(Abramowitz , 2017(Abramowitz , 2019Kroeger, La Mattina 2017;Lundborg et al 2017); cost-benefit assessments of technology (Baird et al 2015;Knies et al 2015;Kulikov et al 2017;Settumba et al 2019). Russian publications are mostly descriptive and introduce readers to the dynamics of technology development in Russia and in the world (Nifantova, Krivenko 2014;Rusanova, Gordeev 2016;Isupova, 2017), and in recent years there have been studies evaluating the benefits of ART for the state (Kulikov et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior work has shown that state insurance mandates affected the general female population by delaying the timing of marriage and childbearing (Schmidt 2007;Ohinata 2011;Abramowitz 2014Abramowitz , 2017, substituting for child adoption (Gumus and Lee 2012), and increasing the probability of pursuing professional education and career (Kroeger and La Mattina 2015). Here, we note that if women are more likely to delay marriage after mandates, and couples who marry later in their life tend to have stable marriages because they have searched for a suitable partner longer and found a better match, this will also help to reduce the divorce probability.…”
Section: Introductionmentioning
confidence: 99%